STUDI KESIAPAN GURU MELAKSANAKAN KURIKULUM 2013 DALAM PEMBELAJARAN BERBASIS TEMATIK INTEGRATIF DI SEKOLAH DASAR SE KECAMATAN COLOMADU TAHUN AJARAN 2014/2015 - Yulia Maftuhah Hidayati; Titik Septiani (Profesi Pendidikan Dasar, 2015)
The study aims to describe 1) teachers’ preparation of implementing an integrativethematicbased learning process, 2) implementing a scientifi c-based learning process, and3) implementing authentic evaluation by the teachers of grade I, II, IV, and V of PrimarySchools of Colomadu Subdistrict. The study employed a qualitative approach. The subjectsincluded the teachers of grade I, II, IV, and V of the schools, and its object was the teachers’preparation of implementing an integrative-thematic based learning process. The datacollection used an interview, observation, questionnaires, and documentation. The techniqueof data analysis applied an interactive model: data reduction, data display and verifi cationand/or conclusion. The results of the study show that the teachers of grade I, II, IV, and V haveunderstood the 2013 curriculum, implemented an integrative and thematicbased learning ascientifi c approach, systematically and implemented a learning preparation based on the 2013curriculum. In terms of an authentic evaluation, the teachers have diffi culties because therewere many students who must be evaluated so that it could not have done comprehensively.